(untitled) (Journal of the College of Basic Education, 2022)
Displacement remains a constant topic of conversation as long as we are talking about poetry and its aestheticsand the modalities of its formation and construction; Although displacement is a product of modern civilization, it is of ancient rootsAnd the concept, especially in the ancient Arab critical discourse, which used terms and sayings that meetMuch with (Cohen) in his term, as is the case with the term breadth in meaning for SibawayhAl-Jurjani’s reversal, or the director’s saying that is not the way out, is the habit of Ibn Rushd, as well as he walkedThe talk of many Arab critics is like this. Modern criticism has been used to expressDisplacement is many terms that almost reach eighteen counted by Abd al-Salam al-Masdi inThe book of style and stylistics (deviation, transgression, transgression, disappointment of expectation and expectation)